Heat moisture treatment-induced changes in feed: A meta-analysis of effects on in vitro rumen fermentation - Rahmadani Mardiah; Susanto Irwan; Fidriyanto Rusli; Jayanegara Anuraga (BIO Web of Conferences)
Heat Moisture Treatment (HMT) is a promising approach to improve the efficiency of concentrate feed in ruminants by inducing changes in feed composition and in vitro rumen fermentation. This meta-analysis evaluates the impact of HMT on feed, focusing on fermentation characteristics and methane emissions. Data from the Scopus database were analyzed using a fixed-effect model, suitable for synthesizing studies with comparable conditions. HMT significantly reduces feed starch content (p<0.001), altering its nutritional profile. It decreases total volatile fatty acids (VFAs) (p<0.05), including acetate, propionate, and butyrate, and shifts the acetate-to-propionate ratio. These changes, alongside reduced ammonia, suggest benefits for rumen health, such as mitigating acidosis risk and improving feed efficiency. However, HMT negatively affects the digestibility of dry matter and organic matter, which may reduce nutrient availability. No significant effects were observed on crude protein digestibility or methane production. While HMT shows potential to enhance feed efficiency and support metabolic health, the trade-offs between reduced digestibility and fermentation benefits highlight the need for further research. These findings provide insights into balancing nutritional and metabolic outcomes when using HMT in ruminant diets.